Investigating the effect of electric field amplitude on the thermal behavior of paraffin/Cu nanostructure in a tube containing non-connected rotating ribs using molecular dynamics simulation - Ahmed Shawqi Sadeq; Rassol Hamed Rasheed; Shaima Albazzaz; Mohammad N. Fares; Soheil Salahshour; Rozbeh Sabetvand (Case Studies in Chemical and Environmental Engineering)
This research investigates the impact of varying external electric field amplitudes on the atomic and thermal properties of a paraffin/copper composite in a tube with non-interconnected rotating ribs, using molecular dynamics simulation as the primary analytical tool. To ensure model accuracy, a preliminary equilibration phase is conducted for 10 ns under controlled conditions. This stabilized the temperature at 300 K and established a consistent total energy of 1.450 kcal/mol. After equilibration, an analysis examined how varying external electric field amplitudes influenced the thermal properties of composite with 7 % copper concentration. The results indicate that as external electric field amplitudes increased from 0.01 to 0.05 V/m, various parameters of the simulated atomic sample show notable variations. Specifically, maximum density decreased from 0.0848 to 0.0836 atom/Å³, while maximum velocity increased from 0.00496 to 0.00519 atom/Å. Additionally, maximum temperature increases from 770 to 789 K, and heat flux increases from 5.59 to 5.71 W/m2. Thermal conductivity increases from 0.72 to 0.78 W/m·K, and charging time decreases from 6.17 to 5.99 ns. When external electric field amplitude increases from 0.01 to 0.03 V/m, discharge time decreases from 7.16 to 7.05 ns; however, at 0.05 V/m, discharge time slightly increases to 7.09 ns. These findings have practical implications for optimizing materials in thermal management and energy storage systems by tailoring electric field conditions to enhance performance.